Explanatory factors of Eurozone equity ETF tracking error - Josip Arnerić; Luka Osojnik (Ekonomski Vjesnik)
Purpose: According to the existing literature, it remains unclear whether a specific ETF outperforms or underperforms its benchmark index in terms of tracking error, especially during crisis periods. Therefore, this study concentrates on the largest and most liquid Eurozone equity ETF, iShares Euro Stoxx 50, which tracks the Euro STOXX 50 index, with the fundamental objective of identifying explanatory factors of tracking errors during crisis periods, encompassing the COVID-19 pandemic and the onset of the Ukrainian war. Methodology: The added value of current research lies in the utilization of Markov regime switching regression with two-state variables. This approach is supported by the idea that the influence of explanatory factors on tracking error may vary between bearish and bullish regimes, which typically align with non-crisis and crisis periods, respectively. Results: Empirical findings indicate that an increase in volatility led to a stronger decrease in tracking error during periods of market stress than in a bullish regime, while a negative impact of illiquidity on tracking error is similar for both regimes. Unlike a single-regime model, Markov switching exhibits a negative relationship between the net flows and tracking error, as expected. The effect of premium/discount seems to be both positive and negative, but a weaker influence was found during a bearish regime due to herding behavior of investors or higher trading costs. Conclusion: This study relies on an ex-ante approach with its main advantage of providing a forward-looking estimate of tracking error that takes into account changes in market conditions and the ETF’s underlying holdings, unlike historical or ex-post tracking error.